Effect of the cathode potential and sulfate ions on nitrate reduction in a microbial electrochemical denitrification system. (1st June 2016) - Nguyen, Van Khanh; Park, Younghyun; Yang, Heechun; Yu, Jaecheul; Lee, Taeho
Abstract: Recently, bioelectrochemical systems have been demonstrated as advantageous for denitrification. Here, we investigated the nitrate reduction rate and bacterial community on cathodes at different cathode potentials [−300, −500, −700, and −900 mV vs. standard hydrogen electrode (SHE)] in a two-chamber microbial electrochemical denitrification system and effects of sulfate, a common nitrate co-contaminant, on denitrification efficiency. The results indicated that the highest nitrate reduction rates (3.5 mg L −1 days −1 ) were obtained at a cathode potential of −700 mV, regardless of sulfate presence, while a lower rate was observed at a more negative cathode potential (−900 mV). Notably, although sulfate ions generally inhibited nitrate reduction, this effect was absent at a cathode potential of −700 mV. Polymerase chain reaction–denaturing gradient gel electrophoresis revealed that bacterial communities on the graphite-felt cathode were significantly affected by the cathode potential change and sulfate presence. Shinella -like and Alicycliphilus -like bacterial species were exclusively observed on cathodes in reactors without sulfate. Ochrobactrum -like and Sinorhizobium -like bacterial species, which persisted at different cathode potentials irrespective of sulfate presence, were shown to contribute to bioelectrochemical denitrification. This study suggested that a cathode potential of around −700 mV versus SHE would ensure optimal nitrate reduction rate and counteract inhibitory effects of sulfate. Additionally, sulfate presence considerably affects denitrification efficiency and microbial community of microbial electrochemical denitrification systems.